Recreational culture as a component of physical education of students of technical higher education institutions - Grokhova, G. (Problems of Engineer-Pedagogical Education, 2020)
The purpose of training future specialist in higher education is to encourage the formation of harmoniously developed, creative personality of the student, able to handle complex pedagogical situations, make the right decisions quickly, and use modern technologies. At the same time, it should be noted that an important factor of vocational training of future specialists is health. Students should take care of their health, perceive it as a value, so acquiring health-related skills is an integral characteristic of the functional state of the human body, which characterizes the ability to perform certain professional activities with a given efficiency and duration during the training period as well as to resist and adapt to unfavorable factors concomitant in these activities. The main indicator of the occupational health for the future specialist is the ability to work. The success of the professional activity for the future specialist is significantly influenced by the physical condition of the body, which depends on the indicators of physical development. All this directly depends on the physical activity, the ability of students to independently do regular recreational activities, which occupy an important place in the structure of professional activity of the future specialist. Recreation itself is aimed at using physical culture as a means of strengthening and developing physical and spiritual qualities of students, relaxation, communication, forms of training. The knowledge gained while conducting the present research allows defining recreation as voluntary physical activity which involves physical exercises aimed at enhancing performance, quality of entertainment and overall improvement of students' personality in the process of vocational training. The designed method of developing recreational culture of students of technical higher education institutions will be significantly improved if in the course of vocational training it is enhanced with corresponding pedagogical conditions.